Potensi Waste to Energy Sampah Perkotaan untuk Kapasitas Pembangkit 1 MW di Propinsi DIY - Wira Widyawidura; Jovita Irene Pongoh (Universitas Janabadra, 2016)
The aim of this work was to study the potential of the waste to be converted into electrical energy (waste to energy) with a target capacity of the biomass power plant (PLTBiomassa) of 1MW. This study was focused in DIY province-Indonesia and the organic waste type used is municipal solid waste (MSW) that collected at the landfill area. The method used inthis paper is by calculating the number of waste based on the composition of waste and finding the potential of electrical power that can be converted from each type of waste through thermochemical and biochemical conversion process. The amount of waste collected in the landfill in DIY province have been sufficient to fulfill target of 1 MW electrical power. The potential of power generated by MSW in landfill are 1541.97 kW generator with 1039.95 kW for thermochemical system (gasification technology) and 502.02 kW for biochemcal system (anaerobic digestion).